Patterns of failure and long-term outcome of postoperative radiotherapy on the survival of patients with pathological T3N0M0 esophageal cancer - Song, Chunyang; Zhu, Shuchai; Xu, Jinrui; Su, Jingwei; Zhang, Xueyuan; Deng, Wenzhao; Zhao, Xiaohan; Shen, Wenbin (Frontiers in Surgery, 2022)
Purpose: The prognostic effect of postoperative radiotherapy (PORT) on pathological T3N0M0 (pT3N0M0) esophageal squamous cell carcinoma (ESCC) remains inconclusive. This study aimed to retrospectively investigate patterns of failure and whether PORT after R0 resection improves survival in patients with pT3N0M0 ESCC, compared with surgery alone. Patients and methods: The clinical data of 256 patients with pT3N0M0 ESCC from January 2007 to December 2010 were retrospectively reviewed. The included patients were classified into two groups: the surgery-plus-postoperative radiotherapy group (S+R) and the surgery-alone group (S). Propensity score matching (PSM) was used to create comparable groups that were balanced across several covariates (n=71 in each group). Statistical analyses were performed using the Kaplan–Meier method and Chi-squared test. Results: In the study cohort, the 5- and 10- year overall survival (OS) rates in the S+R group were 53.4% and 38.4%, and those in the S group were 50.3%, 40.9% (p =0.810), respectively. The 5- and 10- year disease-free survival (DFS) rates in the S+R group were 47.9% and 32.9%, and those in the S group were 43.2%, 24.0% ( p=0.056), respectively. The results were coincident in the matched samples (p=0.883, 0.081) after PSM. Subgroup analysis showed that patients with upper thoracic lesions in the S+R group had significantly higher OS than patients in the S group (p=0.013), in addition, patients with upper and middle thoracic lesions in the S+R group had significantly higher DFS than patients in the S group (p=0.018, 0.049). The results were also confirmed in the matched samples after PSM. The locoregional recurrence between the two groups were significantly different before and after PSM (p=0.009, 0.002). The locoregional control rate (LCR) in the S+R group was significantly higher than that in the S group before and after PSM (p=0.015, 0.008). Conclusion: Postoperative radiotherapy may be associated with a survival benefit for patients with pT3N0M0 upper thoracic ESCC. A multicenter, randomized phase III clinical trial is required to confirm the results of this study.